Association between diabetes-specific health literacy and health-related quality of life among elderly individuals with pre-diabetes in rural Hunan Province, China: a cross-sectional study. Issue 8 (27th August 2019) - Hu, Zhao; Qin, Lulu; Xu, Huilan
Abstract : Objectives: To examine the association between diabetes-specific health literacy (DSHL) and health-related quality of life (HRQoL) among elderly individuals with pre-diabetes in rural China. Design, setting and participants: This cross-sectional study included 434 elderly individuals with pre-diabetes from 42 villages in rural China. Main outcome measures: HRQoL was assessed using the Medical Outcomes Study 36-Item Short-Form Health Survey. DSHL was measured by a validated questionnaire in China. Differences in HRQoL between groups with and without high DSHL were tested by multivariate analysis of covariance (MANCOVA). Results: The prevalence of pre-diabetes was 21.5%. The average age of participants (n=434) was 69.4±6.4 years, and 58.5% were female. Bivariate analysis showed that those with high DSHL had increases of 2.9 points in the physical health component score and 4.4 points in the mental health component score (MCS) compared with those without. After adjustment for potential confounders, a significant MANCOVA model (Wilks' λ=0.974, F=5.63, p=0.004) indicated that individuals with pre-diabetes who had high DSHL reported higher MCS (Mdiff =3.5, 95% CI 1.8 to 6.3, effect size=0.38). This remained significant across subscales: general health (p=0.028), vitality (p=0.014), social functioning (p=0.017) and mental health (p=0.005). Conclusions: Low DSHL was associated with worsening HRQoL among elderly individuals with pre-diabetes in rural China, particularly in the mental health components. Trial registration number: ChiCTR-IOR-15007033.